A global assessment of change in flood volume with surface air temperature. (July 2022) - He, Wei; Kim, Seokhyeon; Wasko, Conrad; Sharma, Ashish
Highlights: In most of the world, flood volume declines as temperatures (T) rise. Large catchments (> 1000 km 2 ) in tropics face water quantity reductions with rising T. In contrast, small catchments in the tropics face more severe flooding due to rising T. Abstract: Climate change is expected to have a significant impact on water security, with higher temperatures causing both enhanced droughts and flood extremes. Here, using global flow data from non-urban catchments, we investigate the sensitivity of flood volume to changes in concurrent surface air temperature. We find most of the world shows decreases in flood volumes with increasing temperature. To understand why this correlation exists, we assess the sensitivity of the above result to mean daily temperatures (climate region), catchment size, and severity of the flood event. Our results indicate that most of the world shows decreases in flood volume with rising temperature for frequent events (50th percentile in this study) and a lesser decrease for rarer events. Changes in the flood volume in tropical regions show the greatest sensitivity to flood percentiles and catchment size. Large catchments in the tropics (≥ 1000 km 2 ) have considerable sensitivities of flood volume with temperature at rates of -10 to -5%/ °C for frequent events (< 90th percentile) whereas small catchments (1000 km 2 ) have sensitivities that only -5%/ °C or greater (i.e., less magnitude). On the other hand, when temperature increases, smaller catchments in the regions are likely to be exposed to more severe flooding at rates up to 15%/ °C for the most severe floods (99.99 percentile in this study) while the rate for large catchments approach zero. Although this study does not seek to find a causality between air temperature and flood runoff, the results suggest a possible decrease in water security with climate change, particularly in large tropical catchments.